KONSEP HUKUM MODERN: SUATU PERSPEKTIF KEINDONESIAAN, INTEGRASI SISTEM HUKUM AGAMA DAN SISTEM HUKUM NASIONAL - Nasarudin Umar (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2014)
Indonesia is known as a country with a mixed legal system. The current legal system is dominated by three major legal systems, namely Western legal system, customary legal system and Islamic legal system. The mixing of legal systems has been an emerging problem, because basically each legal system has a different character. The most basic problem is unbalancing in the formation of legal system in consequence of the dominance of Western legal system from customary and religious legal system. This paper try to analyze the concept of integration of religious legal system in the national legal system to make its position can be balanced. Based on the analysis, the concept of Three Pillars of Modern Legal Systems is suitable for the modern Indonesian legal system in order to integrate the diversity of cultures, customs and religions.